Creating Higher Burdens: Th e Presumption of State Protection in Democratic Countries. - Jamie Chai Yun Liew (Refuge, 2011)
The author examines the burden on refugee claimants at the Immigration and Refugee Board in Canada to provide evidence that their home state cannot protect them. In particular, the paper discusses the growing trend of adjudicators taking de facto judicial notice of the fact that a country is democratic to make the finding that there is state protection for claimants. The author argues that the practice of labelling countries as democratic and making state protection findings upon the finding is a biased and unhelpful practice when evaluating the issue of whether state protection exists. The paper discusses what “democracy” means and the problems associated with defining it. It will discuss how judicial notice of whether a state is democratic can affect an analysis of state protection in the example of claimants fleeing domestic abuse in Mexico.